2007
DOI: 10.1111/j.1447-0594.2007.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reminiscence group in elderly people with Alzheimer disease and vascular dementia in a community setting

Abstract: This study reports the effects of a reminiscence group program on elderly people with two major types of dementia, Alzheimer's disease and vascular dementia, in a randomized controlled clinical trial with a 6-month follow up. The subjects were 24 participants with Alzheimer's disease and 36 with vascular dementia, and were randomly assigned to an intervention group or a control group. The intervention group followed a reminiscence group program in a geriatric health facility for 8 weeks; the control group foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 18 publications
4
79
0
1
Order By: Relevance
“…In fact, reminiscence therapy among individuals with dementia is usually conducted in groups (Akanuma et al, 2011;Hsieh et al, 2010;Lalanne & Piolino, 2013;Wang, Yen, & OuYang, 2009). Studies about the use of reminiscence interventions found that it improves cognition (Akhoondzadeh, Jalalmanesh, & Hojjati, 2014;Cotelli et al, 2012;Tadaka & Kanagawa, 2007;Woods et al, 2005) decreases depressive symptoms (Chung, 2009;Hsieh et al, 2010;Wang, 2007), decreases behavioral symptoms (Akanuma et al, 2011;Hsieh et al, 2010;Huang, Li, Yang, & Chen, 2009;Wang et al, 2009;Woods et al, 2005;Yamagami, Oosawa, Ito, & Yamaguchi, 2007), promotes happiness (Okumura, Tanimukai, & Asada, 2008), enhances a positive mood (Cotelli et al, 2012;O´Rourke, Tobin, O´Callaghan, Sowman, & Collins, 2011;Woods et al, 2005) and facilitates communication (Huang et al, 2009;O´Rourke et al, 2011;Okumura et al, 2008).…”
Section: Reminiscence Therapy In Cognitive Declinementioning
confidence: 97%
“…In fact, reminiscence therapy among individuals with dementia is usually conducted in groups (Akanuma et al, 2011;Hsieh et al, 2010;Lalanne & Piolino, 2013;Wang, Yen, & OuYang, 2009). Studies about the use of reminiscence interventions found that it improves cognition (Akhoondzadeh, Jalalmanesh, & Hojjati, 2014;Cotelli et al, 2012;Tadaka & Kanagawa, 2007;Woods et al, 2005) decreases depressive symptoms (Chung, 2009;Hsieh et al, 2010;Wang, 2007), decreases behavioral symptoms (Akanuma et al, 2011;Hsieh et al, 2010;Huang, Li, Yang, & Chen, 2009;Wang et al, 2009;Woods et al, 2005;Yamagami, Oosawa, Ito, & Yamaguchi, 2007), promotes happiness (Okumura, Tanimukai, & Asada, 2008), enhances a positive mood (Cotelli et al, 2012;O´Rourke, Tobin, O´Callaghan, Sowman, & Collins, 2011;Woods et al, 2005) and facilitates communication (Huang et al, 2009;O´Rourke et al, 2011;Okumura et al, 2008).…”
Section: Reminiscence Therapy In Cognitive Declinementioning
confidence: 97%
“…Consequences are events that occur as a result of the concept. There are many documented consequences of reminiscence, some of which are that it aids positive mental health, aids successful adaptation to old age, reaffirms a sense of identity, maintains self esteem, improves communication skills, increases interaction between individuals, facilitates preparation for death, helps to master personal losses experienced in later life, facilitates important decision making, allows for examination of one's conscience, prepares for the future, and evaluates a past life (Bohlmeijer et al, 2007;Cappeliez et al, 2001Cappeliez et al, , 2005Cappeliez et al, , 2008Egan et al, 2007;Lai et al, 2004;Schweitzer & Bruce, 2008;Serrano et al, 2004;Swee Hong & Heathcote, 2005;Tadaka & Kanagawa, 2007;Thorgrimsen, Schweitzer, & Orrell, 2002;Woods et al, 2005;Yamagami et al, 2007;Zauszniewski et al, 2004).…”
Section: Related Conceptsmentioning
confidence: 96%
“…Reminiscence therapy remains controversial, individually or in group, on past life events of the patient helped by using external aids such as photographs, household items, music and sound recordings, or other familiar items from the past. The final goal is to improve the psychological well-being, mood, and coping skills of patients with AD [128]. Researches have shown that reminiscence is useful to improve directly emotions in overall mood, thus can improve cognitive functioning [129][130][131][132].…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%